Persepsi Guru Terhadap Implementasi Kurikulum Merdeka Di Wilayah 3T: Studi Kasus SD Negeri Juanga, Pulau Morotai - Hi. Muhammad, Fitri Dwi Rahmadhani; Djaguna, Fahmi; Sarapung, Risky Richlos (Peneliti.net, 2025)
This study aims to uncover teachers' perceptions of the implementation of the Independent Curriculum in the 3T (Underdeveloped and Remote Areas) region, focusing on a case study of Juanga Public Elementary School on Morotai Island. Using a descriptive qualitative approach, data were obtained through in-depth interviews, non-participatory observation, and document analysis. The results indicate that teachers have positive perceptions of the Independent Curriculum because it provides flexibility in learning and is oriented towards student character development. However, limited training, infrastructure, and resources hinder its implementation. A key finding of this study is the utilization of local potential as a curriculum adaptation strategy, which has proven effective in supporting project-based learning in remote areas. This confirms that the success of education policy implementation is determined not only by national policies but also by teachers' creativity in managing local resources. This research contributes to the development of education policy implementation theory and provides practical recommendations for the government in designing more contextual training programs for teachers in the 3T (Underdeveloped and Remote Areas) region.